2013
DOI: 10.1002/ppul.22844
|View full text |Cite
|
Sign up to set email alerts
|

Aerosolized KL4surfactant improves short-term survival and gas exchange in spontaneously breathing newborn pigs with hydrochloric acid-induced acute lung injury

Abstract: AERO KL4 S produced similar improvements in survival, physiology, inflammatory markers, and morphology as ETT KL4 S in an ALI model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…However, surface activity of the recombinant SP-C surfactant has recently come under attack after disappointing results in clinical studies of patients with acute lung injury (Spragg et al, 2011). A recent study (Lampland et al, 2014) in spontaneously breathing newborn pigs with acute lung injury showed similar improvements in short-term survival and pulmonary gas exchange with aerosolized and intratracheally instilled liquid KL 4 surfactant (Surfaxin ® , Discovery Laboratories Inc., Warrington, PA, USA). However, the oxygenation response in the spontaneously breathing newborn pigs was rather limited with PaO 2 values ∼200 mm Hg, indicating the limited surface activity of KL 4 -based surfactant mixtures (Walther et al, 1998).…”
Section: Discussionmentioning
confidence: 91%
“…However, surface activity of the recombinant SP-C surfactant has recently come under attack after disappointing results in clinical studies of patients with acute lung injury (Spragg et al, 2011). A recent study (Lampland et al, 2014) in spontaneously breathing newborn pigs with acute lung injury showed similar improvements in short-term survival and pulmonary gas exchange with aerosolized and intratracheally instilled liquid KL 4 surfactant (Surfaxin ® , Discovery Laboratories Inc., Warrington, PA, USA). However, the oxygenation response in the spontaneously breathing newborn pigs was rather limited with PaO 2 values ∼200 mm Hg, indicating the limited surface activity of KL 4 -based surfactant mixtures (Walther et al, 1998).…”
Section: Discussionmentioning
confidence: 91%
“…The success of rescue therapy for chemical-induced ALI using synthetic surfactant with advanced and robust SP-B and SP-C mimics represents a significant breakthrough, as previous experiments have indicated only minimal or no improvement in lung function with animal-derived and first generation synthetic surfactant preparations (Lamm & Albert, 1990; Brackenbury et al, 2001; Zimmermann et al, 2010; Lampland et al, 2014). Lamm & Albert (1990) tested Survanta, a modified natural surfactant based on a bovine lung extract, in rabbit lungs after intratracheal injection of HCl, but found no improvement in arterial oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…Brackenbury et al (2001) treated rabbits pretreated with intratracheal HCl with natural ovine surfactant, bovine lipid extract surfactant and recombinant SP-C surfactant (Venticute) and found none of them effective. Recent studies by Zimmermann et al (2010) and Lampland et al (2014) compared intratracheal instillation and aerosol delivery of KL4 surfactant (Surfaxin ® , Discovery Laboratories, Warrington, PA) with continuous positive airway pressure (CPAP) only in newborn pigs with acute lung injury after HCl instillation. Both KL4 preparations improved survival, but arterial oxygenation did not increase very much over the surfactant pretreatment values.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of jet and ultrasonic nebulizer administration of Exosurf and Survanta in rabbits after lavage lung injury demonstrated significant differences in the amount of drug delivered determined by both the type of nebulizer (ultrasonic Ͼ jet) and the specific surfactant (Exosurf Ͼ Survanta). 20 Irrespective of delivery method, however, neither drug had 21 Survival, lung histology, and interleukin-8 levels were all better with aerosolized and instilled KL4 surfactant relative to a control population supported by CPAP alone. Ruppert et al 22 used a powder aerosolizer with Venticute, an artificial surfactant with recombinant surfactant protein C, in both lung lavage and bleomycin rabbit injury models and showed rapid normalization of oxygenation to pre-injury levels.…”
Section: Aerosolized Surfactants Anti-inflammatory Drugs and Analgementioning
confidence: 99%